Actio Pauliana sebagai Bentuk Perlindungan Hukum bagi Kreditur Kepailitan - Khaqiqi, M. Ikhfal; Elsina L, Rosalinda (CV. Era Digital Nusantara, 2024)
Actio Pauliana is a right owned by creditors, that creditors can, in certain circumstances, view acts that have been carried out by debtors as being null and void. In a bankrupt estate, the authority to file an Actio Pauliana lawsuit is the curator. In practice, in court it is not easy to file an actio pauliana lawsuit until it is granted by the judge. So there are legal issues related to how the legal protection will be for creditors if the Actio Pauliana lawsuit is rejected by the court. This research was carried out in a descriptive normative manner using a statutory, conceptual and case approach. So in the event that the Actio Pauliana lawsuit is rejected by the court, in this case the creditor still has to hand over the affairs of the bankrupt debtor's assets to the Curator who is supervised by the Supervisory Judge. Furthermore, based on the Bankruptcy Law and PKPU, if the bankrupt debtor is proven to have acted in bad faith at the suggestion of the Supervisory Judge, at the request of the Curator, or at the request of one or more creditors and after hearing from the Supervisory Judge, he can order that the Bankrupt Debtor be detained.